Research and Application of Corrosion Prevention Technology for Underground Water Intake Pipelines Based on ICCP (Impressed Current Cathodic Protection) - Wang Zhiliang (PT Publikasiku Academic Solution, 2025)
Underground water intake pipelines play a critical role in supporting the operational reliability of the IPP Sumsel-5 facility, including reuse water, service water, and fire protection systems. These pipelines supply essential resources such as boiler feedwater, steam support, and fire safety, making their integrity vital for continuous plant operations. However, prolonged underground service exposes them to severe corrosion risks that may lead to leaks, water loss, reduced system performance, and potential equipment damage. This study aims to analyze and implement an effective corrosion prevention strategy using Impressed Current Cathodic Protection (ICCP) technology to enhance pipeline lifespan and operational safety. A field-based engineering assessment was conducted involving soil resistivity measurement, pipeline potential testing, corrosion rate evaluation, and system modeling to identify the extent of corrosion threats. The ICCP design framework included anode bed configuration, current output determination, rectifier sizing, and protection potential optimization suited to site-specific soil characteristics. Data collection and analysis were performed through on-site inspection, electrochemical measurement, and simulation-based verification. The results show that the application of ICCP significantly improved the protection potential of the pipelines, maintaining the recommended - 850 mV (Cu/CuSO4) criterion and reducing corrosion progression to a negligible rate. The optimized ICCP system demonstrated stable current distribution, extended pipeline service life, and reduced maintenance risks. Overall, this study confirms that ICCP technology provides a reliable and effective solution for mitigating underground pipeline corrosion at IPP Sumsel-5 and can be adopted as a long-term corrosion management strategy.